Quality of service and customer satisfaction in family businesses. Case: Distribuidora de gas Lidia, in 2019-2020 - Tinco Rojas, Lidia Estela (2022)
Nowadays, the market recognizes that the customer has become the protagonist and the assessment that he makes of the products and / or services takes on greater importance, thus being considered an important factor for the interests of the companies. Therefore, the present study aimed to determine the interaction between service quality and buyer satisfaction; Likewise, understanding how these two components contribute positively to a family business, in this case, the gas distributor “Lidia”, allowing it to grow. The focus of the study is quantitative and non-experimental design, transactional type because it was analyzed in a limited period. In the same way, the scope of the research is correlational since the interaction between the variables is sought. Likewise, the data collection was carried out by using the questionnaire applied to a total sample of 114 clients and whose reliability of the instrument was measured by means of the Cronbach's Alpha index giving a value of 0.950. Finally, the results were validated with statistical tests, concluding that the quality of the service is directly related to the customer satisfaction of the gas distributor “Lidia”.